The effect of motivation, work stress, and self esteem on employee performance through locus of control - Friska Intan Sukarno; Djawoto Djawoto; Prijati Prijati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
This study aimed to investigate the effect of motivation, work stress, and self-esteem on employee performance through locus of control at PT. Procity Surabaya. The population of this study were employees of PT. Procity that involves several divisions, such as: marketing, accountants, tax, legal, and public relations. The sampling technique was purposive sampling that observed 90 employees as samples. Moreover, the analysis technique applied a data processing application, i.e., the SmartPLS 3.0 As the results of data analysis, this study indicated that the motivation had significant effect on employee performance; the work stress had insignificant effect on employee performance; the self-esteem had significant effect on employee performance, the motivation had insignificant effect on employee performance through locus of control; the work stress had insignificant effect and on employee performance through locus of control; and the self-esteem had significant effect on employee performance through locus of control.